Quality Analysis of 5.56 mm Ammunition Defect using Taguchi Method: A Review - Anggamawarti, Merlina Fitri; Alviari, Luana Putri; Sanjiwani, Yudistira; Risonarta, Victor Yuardi (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
In a manufacturing company, the quality loss is estimated by considering the number of defects. Taguchi is a method that finds strong conditions in uncontrollable environments of the field. Taguchi quantifies quality loss through a quality loss function. The Taguchi method particularly is focused on industrial processes. The method is actualizing quality philosophy for continuous quality improvement and cost reduction to improve manufacturing performance. The analysis is designed using Taguchi technique which is related to quality. A high-quality product has a minimal defect. The Taguchi method is used to analyze several defects of ammunition to reduce the number of ammunition defects. Ammunition consists of several parts are called projectile or bullet, cartridge case, propellant charge, and primer. Every part of its process possibly contributes to any defect. The defect type in every part of ammunition consists of critical, major, and minor defects. This paper is focused on cartridge case caliber 5.56 mm defect by using the Taguchi method. The quality characteristic of the experiment result used is smaller the better.Â Critical to Quality (CTQ) is determined to get a critical defect for cartridge cases such as split and perforated case. The influencing factors are brass cup thickness, hardness case after annealing, and annealing temperature. The Taguchi method is effective in reducing defects for the ammunition process to produce a good quality product.